Thermotropic reentrant isotropic symmetry and induced smectic antiferroelectricity in the ferroelectric nematic material RM734 - Xi Chen; Min Shuai; Bingchen Zhong; Vikina Martinez; Eva Korblova; Matthew A. Glaser; Joseph E. Maclennan; David M. Walba; Noel A. Clark (Proceedings of the National Academy of Sciences, 2025)
We report a transition from the ferroelectric nematic liquid crystal (N F ) phase to a lower-temperature, apolar fluid phase having reentrant isotropic symmetry (I R ), in the liquid crystal compound RM734 doped with small concentrations of the ionic liquids 1-Butyl-3-methylimidazolium hexafluorophosphate (BMIM-PF 6 ) or 1-Ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIM-TFSI). Even a trace amount of ionic liquid dopant facilitates the kinetic pathway for the transition from the N F to the I R , enabling simple cooling to produce this isotropic fluid phase rather than resulting in immediate crystallization. The I R was also obtained in the absence of specific ionic liquid doping by appropriate temperature cycling in three distinct, as-synthesized-and-purified batches of RM734, two commercial and one from our laboratory. Ionic liquid doping also stabilizes the smectic Z A , an additional birefringent antiferroelectric phase having the director parallel to fluid smectic layers, significantly increasing its temperature range between the paraelectric and ferroelectric nematic phases with increasing BMIM concentration.